Analisis Pengaruh Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (Pbb-P2) Pajak Bea Perolehan Hak Atas Tanah dan Bangunan (Bphtb) dan Pajak Penerangan Jalan Terhadap Pendapatan Asli Daerah Kabupaten Alor Periode 2018 – 2022 - Abraham Th. Pandu (Peneliti.net, 2023)
This study aims to determine the effect of Rural and Urban Land and Building Tax, Customs Tax on Acquisition of Land and Building Rights, and Street Lighting Tax, on Local Revenue of Alor district for the period 2018 – 2022. This type of research is qualitative research with data collection techniques, namely observation, interviews, and documentation studies. This study uses secondary population data and the sample is Regional Original Income for the 2018-2022 period. The statistical method used in this study is multiple linear regression by looking at the significant value of the t test and the significant value of the F test as a benchmark in making hypotheses and the results of data management using the help of the IBM Spss 22 For Windows program. The results of this study indicate that: partially the variable Rural and Urban Land and Building Tax (PBB-P2) has a significance value of 0.000 or 0.0% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H1 which states that the variable Rural and Urban Land and Building Tax (PBB-P2) partially has a positive effect on Alor Regency Regional Original Income. partially the variable Tax on Acquisition of Land and Building Rights (BPHTB) has a significant value of 0.001 or 0.1% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H2 which states that the Tax variable Land and Building Rights Acquisition Fee (BPHTB) partially has a positive effect on Local Revenue of Alor Regency (partially the Street Lighting Tax variable has a significant value of 0.000 or 0.0% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H3 which states that the variable Street Lighting Tax partially has a positive effect on Local Revenue Alor Regency Simultaneously the variables of Rural and Urban Land and Building Tax, Tax on Land and Building Rights Acquisition Fees, and Street Lighting Tax has a significant value of 0.000 or 0.0% where this value is smaller than the alpha value which is equal to 0.05 which is 5% so that the results of this study simultaneously accept H4 which states that the variables of Rural and Urban Land and Building Tax, Tax on Rights Acquisition on Land and Buildings, and Street Lighting Tax simultaneously have a positive effect on Local Revenue Alor Regency.